Polymerization of lactide to Polylactic acid by using homogenous and heterogenous catalysts on the effect of temperature: article - Mohamed, Alia Syazana; Ibrahim, Norliza; Suhaidi, Amira Nadzirah (2019)
Polylactic acid (PLA) shows a promising alternative to petroleum-based polymers such as plastics. Catalyst such as tin octoate is most common and widely used in synthesizing of PLA in the industrial application using ring-opening polymerization method. The polymerization take place in homogenous phase where the catalyst and the lactide are mixed in liquid phase to form the PLA. However, this method become problematic for the product because the catalyst will remain in the PLA and causes the degradation of the catalyst. The objectives of the research are to investigate the production of PLA by using homogenous and heterogenous catalysts with variation of temperature from 110℃ to 130℃ and to characterize the PLA produced by using Ultraviolet Visible (UV-Vis) Spectrometer and Fourier Transform Infrared Spectroscopy (FTIR). From the result collected, it can be concluded that the synthesis using heterogenous catalyst is better than homogenous catalyst with high concentration and the optimum production of PLA produced is at the highest concentration which is 90.1 ppm with temperature of 130℃ by using heterogenous catalyst.